Quantitative analysis of changes in antioxidant in crosslinked polyethylene (XLPE) cable insulation material exposed to heat and gamma radiation. (October 2018) - Liu, Shuaishuai; Veysey, Stephen W.; Fifield, Leonard S.; Bowler, Nicola
Abstract: Quantitative analysis of the antioxidant poly(1, 2-dihydro-2, 2, 4-trimethylquinoline) (pTMQ) was conducted on pristine, thermally-aged, and gamma radiation-aged commercial cross-linked polyethylene-(XLPE-)based cable insulation material aged at temperatures 60, 90, and 115 °C, with gamma radiation exposure dose rates of 0, 120, 300, and 540 Gy/h for 15 days. The quantification of antioxidant was performed using pyrolysis gas chromatography-mass spectrometry (Py-GCMS). Oxidation induction time (OIT) was measured using differential scanning calorimetry (DSC) and correlation was made between the quantified depletion of antioxidant and measured OIT. It was observed that, in the case of isothermal aging, the quantity of antioxidant and OIT decreased with increasing gamma radiation dose. In the case of samples exposed to the same gamma radiation dose, the quantity of antioxidant and OIT were observed to decrease with increasing aging temperature. Depletion in the quantity of antioxidant relative to that in the pristine material ranged from 7 to 93% for differently aged samples. The measured decline in OIT ranged from 0 to 80%. Change in the quantity of antioxidant in the material was observed to follow the same trend as the change in OIT when the samples were aged under various conditions. The observations are explained in terms of the reaction between the antioxidant and free radicals created during exposure of the samples to thermal and gamma radiation. Highlights: Antioxidant quantity and oxidation induction time declined with increasing gamma radiation dose. Antioxidant quantity and oxidation induction time declined with increasing aging temperature. Changes in antioxidant quantity and oxidation induction time have correlation coefficient 0.82. Depletion of antioxidant is a factor that contributes to changing oxidation induction time of XLPE.